With a Theoretical Approach to the Organization of Marketing Research in the Market of Higher Education Services - Shukrullayevna, Nasriddinova Dildora (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
In this article, marketing tools used directly to disseminate advanced educational ideas, the development of education as a branch of the economy and every state institution, the development of educational services, their quality, and access to them are considered.